1993
DOI: 10.1002/jmv.1890410307
|View full text |Cite
|
Sign up to set email alerts
|

Serologic markers of viral hepatitis A, B, C, and D in patients with hemophilia

Abstract: Forty-one patients with hemophilia A were studied for the prevalence of serological markers for hepatitis A, hepatitis B, hepatitis C (non-A and non-B hepatitis), and delta hepatitis (hepatitis D). Ten of 41 (24.4%) patients demonstrated hepatitis A antibody and 31 of 41 (75.6%) patients had a serologic marker for previous hepatitis B infection; four of these 31 patients (13%) also demonstrated antibody to delta agent (hepatitis D). Thirty-seven of 41 (90.2%) patients demonstrated antibody for hepatitis C. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…The high prevalence of infection with HIV [Tsuchie et al, 1985;Kroner et al, 1994], HCV [ Makris et al, 1990;Troisi et al, 1993], and GBV-C [Hanley et al, 1998;Toyoda et al, 1998] has been reported in many studies. The status of serological markers on HBV infection has also been reported [Kumar et al, 1993;Goedert et al, 2002]. However, occult HBV infection in this population has not been examined.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The high prevalence of infection with HIV [Tsuchie et al, 1985;Kroner et al, 1994], HCV [ Makris et al, 1990;Troisi et al, 1993], and GBV-C [Hanley et al, 1998;Toyoda et al, 1998] has been reported in many studies. The status of serological markers on HBV infection has also been reported [Kumar et al, 1993;Goedert et al, 2002]. However, occult HBV infection in this population has not been examined.…”
Section: Discussionmentioning
confidence: 81%
“…High prevalence of infection with hepatitis C virus (HCV) [Makris et al, 1990;Troisi et al, 1993], human immunodeficiency virus (HIV) [Tsuchie et al, 1985;Kroner et al, 1994], and GB virus C (GBV-C) [Hanley et al, 1998;Toyoda et al, 1998] has been reported. A few studies have also been carried out on hepatitis B virus (HBV) infection in this population by serological evaluation [Kumar et al, 1993;Goedert et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…HCV, like HBV, is transmitted by the parenteral route, and the sources of infection include administration of blood or blood products [13][14][15][16], intravenous drug use [17][18][19][20][21] and needle-stick accidents [22,23]. Nosocomial transmission is not a significant cause of infection in developed countries with the exception of hemodialysis patients, 10-60% of whom are infected [24,25].…”
Section: The Risk Of Hbv Infection Among Patients With Hcv Infectionmentioning
confidence: 99%
“…1985 zu einer beträchtlichen Zahl von HCV-Infektionen [57,58,59]. über viele Jahre Blutprodukte erhielten.…”
Section: Blut Und Blutprodukteunclassified